Satisfaction Factors and Farmers' Loyalty to the Virtako 300 SC Pesticide Brand - Rian Priyatno (Budapest International Research and Critics University, 2022)
Insecticide Virtako 300 SC is an insect toxin produced by PT Syngenta Indonesia. Companies that produce pesticides under various trademarks have stiff competition, therefore pesticide companies must be able to maintain loyalty from the pesticide brand by providing satisfaction for their consumers, so that consumers are satisfied with the results of the pesticides they buy so that consumers buy and use these pesticide products. This study aims to 1) determine the characteristics of consumers Virtako 300 SC, 2) determine the level of satisfaction and level of consumer loyalty Virtako 300 SC. The analytical tools used are descriptive analysis, Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI), and Loyalty Pyramid. Based on the analysis using the IPA method, the attributes that have good performance and are considered important by consumers of the Virtako 300 SC brand of pesticide products are the price attributes according to quality, well-known brands, attractive packaging, easily soluble in water, Virtako Pesticides have the ability to complete kills, and easy to find at the farm shop in Quadrant II. Attributes that need to be improved where these attributes are included in Quadrant I, namely the extension attributes of the company. However, overall, based on the results of the CSI calculation, the score is 73.7. The results of the Loyalty Pyramid are quite good, as seen at the higher level, the wider it reaches the Satisfied Buyer level. It means that the farmers who consume the Virtako 300 SC pesticide are loyal enough.